EMERGENCY TREATMENT OF CARBON MONOXIDE POISONING OF WORKERS IN OIL INDUSTRY - Peričević Medić, Sonja; Ljujic, Jovana; Mikov, Ivan; Spanovic, Milorad; Sakac, Sladjana (Halo 194 Scientific Journal of Emergency Medicine, 2020)
Introduction: The aim of this study was to analyze the case of acute CO poisoning in five workers of the oil industry, in a collective accommodation with a presentation of diagnostic, therapeutic and preventive measures. Case report: Due to health problems caused by CO inhalation because of faulty gas installations, the workers were treated during the night by the emergency medical team and on the emergency department. Venous blood samples were taken to measure carboxyhemoglobin (COHb) and gas analysis at admission and after 120 minutes. Parenteral and oxygen therapy through a mask were performed. After the therapy the workers fully recovered. Conclusion: Prompt recognition of poisoning symptoms and initiation of adequate emergency therapy are crucial for a succsesful treatment outcome. The preventive measures in terms of educating workers and implementing of health and safety measures at workplace and in the working environment are extremly important for preventing of these accidents.